Business and Society : Stakeholders, Ethics, Public Policy - Anne T. Lawrence (McGraw Hill, 2014)
In a world economy that is becoming increasingly integrated and interdependent, the relationship between business and society is becoming ever more complex. The globalization of business, the emergence of civil society organization in many nation, and new government regulation and international agreements have significantly altered the job of managers and the nature of strategic decision making within the firm. At no time has business faced greater public scrutiny or more urgent demands to act in an ethical and socially responsible manner than at the present. The materials in this book consist of seven part and nineteen chapter, also completed with some examples of cases in business and society. The first part discuss about business in society includes the corporation and its stakeholders, managing public issues and stakeholder relationship, and the corporation's social responsibilities. The second part discuss about business and ethics includes Ethics and ethical reasoning and organizational ethics and the law. Part three in this book discuss about business in a globalized world include the challenges of globalization and global corporate citizenship. The fourth part discuss business and public policy includes business-government relations and influencing the political environment, The fifth part discuss about business and the natural enviroment. The sixth part discuss about business and technology includes tecnology, organizations, and society, and managing technology and innovation. Part seven discuss about business and its stakeholders includes stockholder rights and corporate governance, consumen protection, employees and the corporation, managing a diverse workforce, the community and the corporation and managing public relation.